LATE ALBIAN FLORA FROM THE VICINITY OF THE PROKHLADNOE VILLAGE (THE CRIMEA) - Doludenko M.P.; Smirnova S.B.; Moiseeva M.G. (My University, 2002)
Paleobotanical and palynological data on the same units seemingly lead to a controversial interpretation of the late Albian flora and vegetation. For instance, an upper part of the upper Albian Hysteroceras orbignyi Zone (the Prokhladnoe Village, the Crimea) reveals abundant impressions of Taxodiaceae shoots (genus Geinitzia) and ferns of the Gleichenia genus, which associate with rare representatives of Schizaeaceae and Dicksoniaceae. At the same time, bisaccate pollen of the Pinaceae, Podocarpaceae, and other families and that of the Schizaeaceae, Dicksoniaceae, Gleicheniaceae ferns dominate in the palynological spectrum of the same unit. So data, similar for ferns, are quite different for conifers: the prevalence of Taxodiaceae among imprints is not reflected in the palynological spectrum, where their pollen is found as single specimens. In turn, the dominance and diversity of bisaccate pollen in the palynological spectrum does not correspond to abundance of these plants imprints, as we found only two of them. The combination of data and the analyzed reasons of their inconsistency make it possible however to reconstruct reliably the late Albian vegetation. As is established, the seacoast in the studied area was covered with various ferns, among which Gleicheniaceae and Schizaeaceae representatives dominated. Abundant Geinitzia shoots found in the area suggest that the coastal band with ferns was not wide, and that coniferous microphyllous forests closely approached the sea. Palynological data indicate a proximity of hill slopes thickly populated by conifers producing the abundant bisaccate pollen. Taken together, these data imply that the relief was rugged and variable, and the climate was warm and humid.
Keywords: Albian; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский